A case study for source identification of oil spilled to the ocean and shoreline near Postville, Labrador, Canada - Zeyu Yang; Keval Shah; Bruce P. Hollebone; Chun Yang; Patrick Lambert; Graham Thomas; Blain Trainor; Vanessa Beaulac (Regional Studies in Marine Science, 2026)

Freshwater biodiversity in a rapidly changing Arctic: An expert horizon scan of key research questions - Joseph M. Culp; Michael Power; Kirsten S. Christoffersen; Willem Goedkoop; Kimmo K. Kahilainen; Milla Rautio; Fernando Chaguaceda; Marie-Pier Hébert; Sanne M. Moedt; Dermot Antoniades; Simon Belle; Daniel Bolnick; et al. (Ambio, 2026)
Arctic freshwater biodiversity is rapidly changing due to climate warming, resource extraction, infrastructure development, and landscape transformation. To improve understanding, predict future responses, and inform policy formulation, research needs must be clearly identified. Using a horizon scan survey, Arctic freshwater experts from government, international agencies, and Indigenous Peoples identified 77 biodiversity research questions with 17 highlighted as most important for near term assessment. These questions span nine thematic categories: biodiversity and taxonomic challenges, hydrological change, productivity and food webs, ecosystem connectivity, methods, monitoring and assessment, permafrost change, winter ecology, anthropogenic development, and Indigenous Knowledge. Climate change emerged as the major driver among all categories and research questions. A key priority identified was the urgent need for long-term, harmonized monitoring programs among Arctic countries. Multiple knowledge gaps detected suggest that circumpolar research collaborations are required to tackle these issues.

Past trajectory of a Northwest Europe socio-ecosystem at the land-sea interface: Case study of the northern watersheds of the Bay of Brest over the last 150 years - C. Valero; A. Penaud; M. Vidal; E. Goubert; P.A. Dessandier; S. Schmidt; E. Glémarec; P. Brigode; L. Bosseboeuf; Y.M. Paulet; J. Sutton; P. Ailliot; et al. (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Systematic review update of organisational-level mental health promotion interventions: evidence from healthcare, construction, and telework-based mobile work settings - Eleftherios Giovanis; Oznur Ozdamar; Birgit Aust; Johanna Cresswell-Smith; Arlinda Cerga Pashoja; Caleb Leduc; Andrea Sinesi; Carolina Piña; Chantal Van Audenhove; Gentiana Qirjako; Victoria Ross; Margaret Kenneally; et al. (International Archives of Occupational and Environmental Health, 2026)

Aquaculture potential evolution during early domestication trials in a model species (Danio rerio) with different breeding strategies - E. Diakos; P. Fontaine; S. Lambert; Y. Ledoré; J. Lambert; A. Magitteri; Md. Shahjahan; P. Kestemont; M. Vandeputte; T. Lecocq (Aquaculture, 2026)

A baseline assessment of the occurrence, characterization, source, and risk impact of petroleum-related hydrocarbons in sediments along the southeast shoreline of Vancouver Island and Southern Gulf Islands in British Columbia, Canada - Zeyu Yang; Keval Shah; Claire Courtemanche; Sonia Laforest; Bruce P. Hollebone; Antoine Rolland; Pascal Hebert; Patrick Lambert; Michael Goldthorp; Yuan Yao; Michael J.J. Murphy; Chun Yang; et al. (Regional Studies in Marine Science, 2025)

Road networks and food price volatility - Lixia H. Lambert; John P. Schoeneman; Dayton M. Lambert; Marten W. Brienen (Global Food Security, 2025)

Association of genetic variants in CYP3A5, DRD2 and NK1R with opioid overdose - Joshua Lambert; Dan Petrovitch; Katie P. Himes; Caroline E. Freiermuth; Robert S. Braun; Jennifer L. Brown; Jason J. Bischof; Michael S. Lyons; Brittany E. Punches; Andrew K. Littlefield; David F. Kisor; Jon E. Sprague (Chemico-Biological Interactions, 2024)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Allicin and total phenolic content in ramps (Allium tricoccum Ait.) in relation to phenological stage, morphological traits, and harvest location - R. Teal Jordan; Eric P. Burkhart; Margot Kaye; David Munoz; Joshua D. Lambert (Biochemical Systematics and Ecology, 2024)

Reliability of recovery heart rate variability measurements as part of the Lamberts Submaximal Cycle Test and the relationship with training status in trained to elite cyclists - Robert P. Lamberts; Teun van Erp; Alejandro Javaloyes; Maaike M. Eken; Nelleke G. Langerak; Nicholas Tam (European Journal of Applied Physiology, 2024)
Purpose To determine if post-exercise heart rate variability, in the form of logged transformed root mean square of successive differences of the R–R intervals (LnRMSSD) can be measured reliably during the recovery from a submaximal cycle test and what the relationship of LnRMSSD is with training status of the cyclists. Methods Fourteen male cyclists participated in the reliability part for the study, which included performing six Lamberts Submaximal Cycle Test (LSCT), during which recovery LnRMSSD was measured over 30 s (LnRMSSD 30 s ), 60 s LnRMSSD 60 s )and 90 s LnRMSSD 90 s ). In addition, fifty male and twenty female cyclists completed a peak power output (PPO) test (including V O 2peak ) and 40 km time trial (40 km TT) before which they performed the LSCT as a standardized warm-up. Relationships between the LnRMSSD and PPO, V O 2peak and 40 km TT time were studied. Results Due to the design of the LSCT, submaximal heart and breathing rate were similar at the end of stage 3 of the LSCT, as well as during the recovery periods. The highest reliability was found in LnRMSSD 60 s (ICC: 0.97) with a typical error of the measurement (TEM: 5.8%). In line with this the strongest correlations were found between LnRMSSD 60 s and PPO ( r = 0.93[male]; 0.85[female]), V O 2peak ( r = 0.71[male]; 0.63[female];) and 40 km TT ( r = – 0.83[male]; – 0.63[female]). Conclusions LnRMSSD 60 s can be measured reliably after the LSCT and can predict PPO, V O 2peak and 40 km TT performance well in trained-to-elite cyclists. These findings suggest that recovery LnRMSSD can potentially play an important role in monitoring and fine-tuning training prescriptions in trained-to-elite cyclists.

Environmental evolution of western Tierra del Fuego (∼54°S) since ice-free conditions and its zonal/hemispheric implications - Patricio I. Moreno; Fabrice Lambert; Loreto Hernández; Rodrigo P. Villa-Martínez (Quaternary Science Reviews, 2023)

The effect of preference and actual days spent working from home on stress and musculoskeletal pain in older workers - Jodi Oakman; Katrina A. Lambert; Victoria P. Weale; Rwth Stuckey; Melissa Graham (International Archives of Occupational and Environmental Health, 2023)
Objectives The rapid shift to working from home (WFH) due to the COVID-19 pandemic provided a unique opportunity to examine the relationship between preferred and actual days spent working from home on employees musculoskeletal pain (MSP) and stress in older workers. Methods This study uses three waves of data from the Employees Working from Home (EWFH) study collected in May 2021 ( n = 451), November 2021 ( n = 358) and May 2022 ( n = 320) during the COVID-19 pandemic. A generalised mixed-effect model was used to model the relationships between preference and actual days spent WFH, stress and MSP. Exploratory mediation analysis was conducted to further explore significant relationships between actual days WFH and outcomes. Results WFH was associated with increasing stress levels in older participants, when the actual number of days WFH increased (B: 0.051, 95% CI: 0.008, 0.094) and when the number of days WFH exceeded their preferences (B: 0.218, 95% CI: 0.087, 0.349). Actual number of days spent WFH and stress in older employees was mediated through their sense of community (Indirect effect: 0.014, 95% CI: 0.003, 0.03; p = 0.006). The relationship between WFH and MSP was variable. For older employees, WFH more than their preferred number of days was associated with a higher likelihood of reporting MSP (OR: 4.070, 95% CI: 1.204, 13.757). Conclusions Findings from this study support the need for flexible policies to support WFH which take into account employees preferences. For older workers, a sense of community was found to be important and proactive attempts to restore this will be important for maintain their health and supporting sustainable employment.

Intentions of Landowners towards Active Management of Ecosystem for Deer Habitat - Bijesh Mishra; Omkar Joshi; Binod P. Chapagain; Lixia He Lambert; Rodney E. Will (Environmental Management, 2023)

Depressed HCN4 function in the type 2 diabetic sinoatrial node - Sajida Parveen; Paddy H. S. Cheah; Luke P. I. Worthington; Roseanna A. Smither; Michelle L. Munro; Carol T. Bussey; Regis R. Lamberts; Peter P. Jones (Molecular and Cellular Biochemistry, 2023)

Ecomorphology of toothed whales (Cetacea, Odontoceti) as revealed by 3D skull geometry - Deborah Vicari; Michael R. McGowen; Olivier Lambert; Richard P. Brown; Giovanni Bianucci; Richard C. Sabin; Carlo Meloro (Journal of Mammalian Evolution, 2023)
Extant odontocetes (toothed whales) exhibit differences in body size and brain mass, biosonar mode, feeding strategies, and diving and habitat adaptations. Strong selective pressures associated with these factors have likely contributed to the morphological diversification of their skull. Here, we used 3D landmark geometric morphometric data from the skulls of 60 out of ~ 72 extant odontocete species and a well-supported phylogenetic tree to test whether size and shape variation are associated with ecological adaptations at an interspecific scale. Odontocete skull morphology exhibited a significant phylogenetic signal, with skull size showing stronger signal than shape. After accounting for phylogeny, significant associations were detected between skull size and biosonar mode, body length, brain and body mass, maximum and minimum prey size, and maximum peak frequency. Brain mass was also strongly correlated with skull shape together with surface temperature and average and minimum prey size. When asymmetric and symmetric components of shape were analysed separately, a significant correlation was detected between sea surface temperature and both symmetric and asymmetric components of skull shape, and between diving ecology and the asymmetric component. Skull shape variation of odontocetes was strongly influenced by evolutionary allometry but most of the associations with ecological variables were not supported after phylogenetic correction. This suggests that ecomorphological feeding adaptations vary more between, rather than within, odontocete families, and functional anatomical patterns across odontocete clades are canalised by size constraints.

Ramp (Allium tricoccum Ait.) weight differs across the harvest season: implications for wild plant stewardship and forest farming - Sarah E. Nilson; Eric P. Burkhart; R. Teal Jordan; Joshua D. Lambert (Agroforestry Systems, 2023)

Towards a genetic theory of island biogeography: Inferring processes from multidimensional community‐scale data - Isaac Overcast; Guillaume Achaz; Robin Aguilée; Carmelo Andújar; Paula Arribas; Thomas J. Creedy; Evan P. Economo; Rampal S. Etienne; Rosemary Gillespie; Claire Jacquet; Flora Jay; Susan Kennedy; et al. (Global Ecology and Biogeography, 2023)
Background MacArthur and Wilson's theory of island biogeography has been a foundation for obtaining testable predictions from models of community assembly and for developing models that integrate across scales and disciplines. Historically, however, these developments have focused on integration across ecological and macroevolutionary scales and on predicting patterns of species richness, abundance distributions, trait data and/or phylogenies. The distribution of genetic variation across species within a community is an emerging pattern that contains signatures of past population histories, which might provide an historical lens for the study of contemporary communities. As intraspecific genetic diversity data become increasingly available at the scale of entire communities, there is an opportunity to integrate microevolutionary processes into our models, moving towards development of a genetic theory of island biogeography. Motivation/goal We aim to promote the development of process‐based biodiversity models that predict community genetic diversity patterns together with other community‐scale patterns. To this end, we review models of ecological, microevolutionary and macroevolutionary processes that are best suited to the creation of unified models, and the patterns that these predict. We then discuss ongoing and potential future efforts to unify models operating at different organizational levels, with the goal of predicting multidimensional community‐scale data including a genetic component. Main conclusions Our review of the literature shows that despite recent efforts, further methodological developments are needed, not only to incorporate the genetic component into existing island biogeography models, but also to unify processes across scales of biological organization. To catalyse these developments, we outline two potential ways forward, adopting either a top‐down or a bottom‐up approach. Finally, we highlight key ecological and evolutionary questions that might be addressed by unified models including a genetic component and establish hypotheses about how processes across scales might impact patterns of community genetic diversity.

Responding to flood risk in Louisiana: the roles of place attachment, emotions, and location - Jason R. Holley; Katherine A. McComas; Catherine E. Lambert; Natalie P. Snider; Grace K. Tucker (Natural Hazards, 2022)
Drawing from protection motivation theory (PMT), we examined how place attachment and negative emotions, alongside threat and coping appraisals, personal experiences, and demographic characteristics, relate to behavioral intentions to mitigate exposure to flood risks in southern Louisiana. We administered a statewide, representative telephone survey to 807 Louisiana residents, oversampling residents living in southern and coastal parishes particularly vulnerable to flood risk. While the results showed no difference depending on participants’ location in the state, there were strong effects of coping appraisals on individuals’ intentions to mitigate their exposure to flood risk, consistent with prior PMT findings. The addition of place attachment to standard PMT variables revealed a nuanced relationship with behavioral intentions. Results show that participants’ place attachment decreased the effects of threat and coping appraisals on some behavioral intentions, such as moving out of the state, while posing no significant effect of threat and coping appraisals on other intentions, such as supporting flood risk mitigation policies. Feeling negative emotions increased the likelihood of participants’ indicating a willingness to move or elevate their home, among other actions. While this study supports the consistency of threat and coping appraisals to predict discrete behavioral intentions, the results also provide insight that may be critical for risk communication initiatives in Louisiana. Namely, individuals with high levels of place attachment may be less willing to leave their community but more willing to engage in behaviors that enhance community resilience, although the more negative emotions they feel, the more willing they may be to take more drastic measures.

Correction to: 2021 Taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Bernard R. Agwanda; Rim Al Kubrusli; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Christopher F. Basler; et al. (Archives of Virology, 2021)

2021 Taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Bernard R. Agwanda; Rim Al Kubrusli; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Christopher F. Basler; et al. (Archives of Virology, 2021)

Correction to: Bacterial etiology of community-acquired pneumonia in immunocompetent hospitalized patients and appropriateness of empirical treatment recommendations: an international point-prevalence study - Manuela Carugati; S. Aliberti; G. Sotgiu; F. Blasi; A. Gori; R. Menendez; M. Encheva; M. Gallego; P. Leuschner; S. Ruiz-Buitrago; S. Battaglia; R. Fantini; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2021)

2020 taxonomic update for phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Daniela Alioto; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Simon J. Anthony; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Tomáš Bartonička; et al. (Archives of Virology, 2020)

Bacterial etiology of community-acquired pneumonia in immunocompetent hospitalized patients and appropriateness of empirical treatment recommendations: an international point-prevalence study - Manuela Carugati; S. Aliberti; G. Sotgiu; F. Blasi; A. Gori; R. Menendez; M. Encheva; M. Gallego; P. Leuschner; S. Ruiz-Buitrago; S. Battaglia; R. Fantini; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2020)

Taxonomy of the order Bunyavirales: update 2019 - Abulikemu Abudurexiti; Scott Adkins; Daniela Alioto; Sergey V. Alkhovsky; Tatjana Avšič-Županc; Matthew J. Ballinger; Dennis A. Bente; Martin Beer; Éric Bergeron; Carol D. Blair; Thomas Briese; Michael J. Buchmeier; et al. (Archives of Virology, 2019)

Effects of optical sensing based variable rate nitrogen management on yields, nitrogen use and profitability for cotton - M. Stefanini; J. A. Larson; D. M. Lambert; X. Yin; C. N. Boyer; P. Scharf; B. S. Tubaña; J. J. Varco; D. Dunn; H. J. Savoy; M. J. Buschermohle (Precision Agriculture, 2019)

Morphological and genetic diversity of cacao (Theobroma cacao L.) in Uganda - David Gopaulchan; Lambert A. Motilal; Frances L. Bekele; Séverine Clause; James O. Ariko; Harriet P. Ejang; Pathmanathan Umaharan (Physiology and Molecular Biology of Plants, 2019)

Taxonomy of the order Bunyavirales: second update 2018 - Piet Maes; Scott Adkins; Sergey V. Alkhovsky; Tatjana Avšič-Županc; Matthew J. Ballinger; Dennis A. Bente; Martin Beer; Éric Bergeron; Carol D. Blair; Thomas Briese; Michael J. Buchmeier; Felicity J. Burt; et al. (Archives of Virology, 2019)

ScalA-FS: expert-based ex-ante assessments of local requirements and success potential of upgrading strategies for improving food security in rural Tanzania - Götz Uckert; Frieder Graef; Anja Faße; Ludger Herrmann; Harry Hoffmann; Frederick C. Kahimba; Luitfred Kissoly; Hannes J. König; Christine Lambert; Henry Mahoo; Bashir Makoko; Leon Mrosso; et al. (Food Security, 2018)

Taxonomy of the family Arenaviridae and the order Bunyavirales: update 2018 - Piet Maes; Sergey V. Alkhovsky; Yīmíng Bào; Martin Beer; Monica Birkhead; Thomas Briese; Michael J. Buchmeier; Charles H. Calisher; Rémi N. Charrel; Il Ryong Choi; Christopher S. Clegg; Juan Carlos de la Torre; et al. (Archives of Virology, 2018)

Differential sensitivity to the antifouling chemical medetomidine between wood frog and American toad tadpoles with evidence for low-dose stimulation and high-dose inhibition of metamorphosis - Peter P. Fong; Olivia J. Lambert; Margot L. Hoagland; Emily R. Kurtz (Environmental Science and Pollution Research, 2018)

Exposure to the antifouling chemical medetomidine slows development, reduces body mass, and delays metamorphosis in wood frog (Lithobates sylvaticus) tadpoles - Janine M. Barr; Julia R. Palmucci; Olivia J. Lambert; Peter P. Fong (Environmental Science and Pollution Research, 2018)

River Continuity Restoration and Diadromous Fishes: Much More than an Ecological Issue - H. Drouineau; C. Carter; M. Rambonilaza; G. Beaufaron; G. Bouleau; A. Gassiat; P. Lambert; S. le Floch; S. Tétard; E. de Oliveira (Environmental Management, 2018)

Alzheimer’s disease and driving: review of the literature and consensus guideline from Belgian dementia experts and the Belgian road safety institute endorsed by the Belgian Medical Association - Jan Versijpt; Mark Tant; Ingo Beyer; Jean-Christophe Bier; Patrick Cras; Peter P. De Deyn; Patrick De Wit; Olivier Deryck; Bernard Hanseeuw; Margareta Lambert; Jean-Claude Lemper; Eric Mormont; et al. (Acta Neurologica Belgica, 2017)

Epiphytic diatoms as indicators of ecological condition in New Zealand’s lowland wetlands - C. Kilroy; A. M. Suren; J. A. Wech; P. Lambert; B. K. Sorrell (New Zealand Journal of Marine and Freshwater Research, 2017)
The condition of New Zealand’s remnant wetlands has been documented by landscape‐scale assessments such as the Index of Ecological Integrity and Wetland Condition Index. We explored the potential for microscopic aquatic biota (epiphytic diatoms) to provide complementary information about wetland condition using data from 77 lowland sites (mainly palustrine swamps) with circumneutral pH. In the South Island, correspondence between diatoms and wetland indices or water quality was weak. In the North Island, conductivity and total dissolved nitrogen (TDN) together explained 49% of the variance in assemblage composition and several diatom genera were indicative of high or low conductivity, dissolved phosphorus and TDN. Changes in these water quality variables may trigger changes in wetland condition, which are eventually reflected by the landscape‐scale indices. Diatoms respond rapidly to water quality changes suggesting potential for diatom indicator taxa to provide early warning of wetland degradation or to track restoration.

Exposure to SSRI-type antidepressants increases righting time in the marine snail Ilyanassa obsoleta - Peter P. Fong; Taylor B. S. Bury; Elizabeth E. Donovan; Olivia J. Lambert; Julia R. Palmucci; Stephnie K. Adamczak (Environmental Science and Pollution Research, 2017)

A zoogeographical boundary between the Palaearctic and Sino‐Japanese realms documented by consistent north/south phylogeographical divergences in three woodland birds in eastern China - Gang Song; Ruiying Zhang; Yanhua Qu; Zhiheng Wang; Lu Dong; Anton Kristin; Per Alström; Per G. P. Ericson; David M. Lambert; Jon Fjeldså; Fumin Lei (Journal of Biogeography, 2016)
Aim The location of zoogeographical boundaries in eastern China has long been the subject of debate. To identify any north/south genetic divergence between the Palaearctic and Sino‐Japanese realms proposed by previous studies, we conducted a comparative phylogeographical study involving three passerine species with wide latitudinal distributions in eastern China. Location Eastern China. Methods Two mitochondrial genes and three nuclear introns were amplified and sequenced. Population structures were analysed using intra‐specific phylogeny, tcs networks, AMOVA and structure inferences. We tested for evidence of genetic barriers based on pairwise differences. Lineage divergences, demographic dynamics and gene flow between lineages were estimated using Bayesian methods. Results A congruent north/south phylogeographical divergence was identified for three species. A geographical barrier was inferred at c . 40° N in eastern China. The population sizes of the northern and southern lineages have both been stable through the late Pleistocene, while multiple divergences were inferred during the early and middle Pleistocene. Main conclusions Our results suggest a general phylogeographical break in north‐eastern China, coinciding with the Palaearctic/Sino‐Japanese boundary. Physical blocking of the Yan Mountains and fragmentation of suitable habitat during glacial stages between the north and south probably acted together to provide long‐lasting barrier effects. Our comparative phylogeographical approach demonstrates that the Palaearctic/Sino‐Japanese boundary may represent a gene‐flow barrier even within widespread species.

The connection of the Indonesian Throughflow, South Indian Ocean Countercurrent and the Leeuwin Current - Erwin Lambert; Dewi Le Bars; Wilhelmus P. M. de Ruijter (Ocean Science, 2016)
East of Madagascar, the shallow “South Indian Ocean Counter Current (SICC)” flows from west to east across the Indian Ocean against the direction of the wind-driven circulation. The SICC impinges on west Australia and enhances the sea level slope, strengthening the alongshore coastal jet: the Leeuwin Current (LC), which flows poleward along Australia. An observed transport maximum of the LC around 22° S can likely be attributed to this impingement of the SICC. The LC is often described as a regional coastal current that is forced by an offshore meridional density gradient or sea surface slope. However, little is known about the controls of these open-ocean gradients. The regional circulation system is embedded in the subtropical “super gyre” that connects the Indo-Pacific via the Tasman Gateway and the Indonesian passages. The Indonesian Throughflow (ITF) circulates through the Indian Ocean back into the Pacific south of Australia. This return pathway appears to be partly trapped in the upper layer north of an outcrop line. It is redirected along this outcrop line and joins the eastward flow of the SICC. To study the connection of the basin-scale and the inter-ocean-scale dynamics, we apply both an ocean general circulation model and a conceptual two-layer model. Shutdown of the ITF in the models leads to a large decrease in Leeuwin Current transport. Most of the SICC was found to then reconnect to the internal gyre circulation in the Indian Ocean. ITF, SICC and LC thus appear to be dynamically connected.

A Discrete/continuous Coupled Approach for Modeling Impacts on Cellular Geostructures - A. Breugnot; S. Lambert; P. Villard; P. Gotteland (Rock Mechanics and Rock Engineering, 2016)

Antarctica on foot: the energy expended to walk, ski and man-haul - L. G. Halsey; R. Lambert; P. Collins; A. Newnham; A. Kumar; C. O’Driscoll; M. A. Stroud (Polar Biology, 2016)

Remembering Jerry Lwanga: A Perspective from His Colleagues - Tony L. Goldberg; Samuel Angedakin; Gilbert M. Isabirye Basuta; Michelle Brown; Thomas M. Butynski; Colin A. Chapman; Lauren Chapman; Sholly Gunter; Innocent Kato; Jean-Michel Krief; Sabrina Krief; Joanna E. Lambert; et al. (International Journal of Primatology, 2016)

Multitrophic enemy escape of invasive Phragmites australis and its introduced herbivores in North America - Warwick J. Allen; Randee E. Young; Ganesh P. Bhattarai; Jordan R. Croy; Adam M. Lambert; Laura A. Meyerson; James T. Cronin (Biological Invasions, 2015)

Climatic and biotic extreme events moderate long‐term responses of above‐ and belowground sub‐Arctic heathland communities to climate change - Stef Bokhorst; Gareth K. Phoenix; Matty P. Berg; Terry V. Callaghan; Christopher Kirby‐Lambert; Jarle W. Bjerke (Global Change Biology, 2015)
Climate change impacts are not uniform across the Arctic region because interacting factors causes large variations in local ecosystem change. Extreme climatic events and population cycles of herbivores occur simultaneously against a background of gradual climate warming trends and can redirect ecosystem change along routes that are difficult to predict. Here, we present the results from sub‐Arctic heath vegetation and its belowground micro‐arthropod community in response to the two main drivers of vegetation damage in this region: extreme winter warming events and subsequent outbreaks of the defoliating autumnal moth caterpillar ( Epirrita autumnata ). Evergreen dwarf shrub biomass decreased (30%) following extreme winter warming events and again by moth caterpillar grazing. Deciduous shrubs that were previously exposed to an extreme winter warming event were not affected by the moth caterpillar grazing, while those that were not exposed to warming events (control plots) showed reduced (23%) biomass from grazing. Cryptogam cover increased irrespective of grazing or winter warming events. Micro‐arthropods declined (46%) following winter warming but did not respond to changes in plant community. Extreme winter warming and caterpillar grazing suppressed the CO 2 fluxes of the ecosystem. Evergreen dwarf shrubs are disadvantaged in a future sub‐Arctic with more stochastic climatic and biotic events. Given that summer warming may further benefit deciduous over evergreen shrubs, event and trend climate change may both act against evergreen shrubs and the ecosystem functions they provide. This is of particular concern given that Arctic heath vegetation is typically dominated by evergreen shrubs. Other components of the vegetation showed variable responses to abiotic and biotic events, and their interaction indicates that sub‐Arctic vegetation response to multiple pressures is not easy to predict from single‐factor responses. Therefore, while biotic and climatic events may have clear impacts, more work is needed to understand their net effect on Arctic ecosystems.

Patterns of herbivory-induced mortality of a dominant non-native tree/shrub (Tamarix spp.) in a southwestern US watershed - Kevin R. Hultine; Tom L. Dudley; Dan F. Koepke; Daniel W. Bean; Ed P. Glenn; Adam M. Lambert (Biological Invasions, 2015)

The potential capacity of French wildlife rescue centres for wild bird disease surveillance - P. Gourlay; A. Decors; M. Moinet; O. Lambert; B. Lawson; F. Beaudeau; S. Assié (European Journal of Wildlife Research, 2014)

Selecting with markers linked to the PPVres major QTL is not sufficient to predict resistance to Plum Pox Virus (PPV) in apricot - S. Decroocq; A. Chague; P. Lambert; G. Roch; J-M. Audergon; F. Geuna; R. Chiozzotto; D. Bassi; L. Dondini; S. Tartarini; J. Salava; B. Krška; et al. (Tree Genetics & Genomes, 2014)

Effect of exercise intensity on post-exercise oxygen consumption and heart rate recovery - Theresa N. Mann; Christopher Webster; Robert P. Lamberts; Michael I. Lambert (European Journal of Applied Physiology, 2014)

Larval morphology and host use confirms ecotypic variation in Cactoblastis cactorum (Berg) - Christopher P. Brooks; Brice H. Lambert; Kristen E. Sauby; Gary N. Ervin; Laura Varone; Guillermo A. Logarzo (Biological Invasions, 2014)

Cationic uremic toxins affect human renal proximal tubule cell functioning through interaction with the organic cation transporter - Carolien M. S. Schophuizen; Martijn J. Wilmer; Jitske Jansen; Lena Gustavsson; Constanze Hilgendorf; Joost G. J. Hoenderop; Lambert P. van den Heuvel; Rosalinde Masereeuw (Pflügers Archiv - European Journal of Physiology, 2013)

Environmental sustainability, complex systems, and the disruptive imagination - Thomas P. Seager; Zachary A. Collier; Igor Linkov; James H. Lambert (Environment Systems and Decisions, 2013)

Case studies of scenario analysis for adaptive management of natural resource and infrastructure systems - Michelle C. Hamilton; Shital A. Thekdi; Elisabeth M. Jenicek; Russell S. Harmon; Michael E. Goodsite; Michael P. Case; Christopher W. Karvetski; James H. Lambert (Environment Systems and Decisions, 2013)

Occurrence of viruses within Tasmanian vegetable crops and identification of a novel Polerovirus infecting pea - C. R. Wilson; S. J. Lambert; A. L. Dann; P. Cross; F. S. Hay (Australasian Plant Pathology, 2012)

Q fever seroprevalence in metropolitan samples is similar to rural/remote samples in Queensland, Australia - S. J. Tozer; S. B. Lambert; T. P. Sloots; M. D. Nissen (European Journal of Clinical Microbiology & Infectious Diseases, 2011)

Temporal variation of invertebrate communities in perennial wetlands - AM Suren; P Lambert (New Zealand Journal of Marine and Freshwater Research, 2010)
Temporal variability of wetland invertebrates was examined at two scales—inter‐annual and seasonal—to determine whether it could confound results of spatially extensive wetland surveys. The inter‐annual study collected samples from the Bullock Creek wetland (BCW) each summer for 4 years; the seasonal study collected samples quarterly for 14 months from two wetlands (Mahinapua and Shearer). Water pH, temperature and conductivity were also measured concurrently. Three site groupings were identified in BCW, reflecting differences in physical–chemical parameters, which varied temporally but never converged. Few annual differences were found in invertebrate relative abundances in BCW, and ordination produced three sample groups, each of which contained distinct invertebrate communities. Water pH differed consistently between Mahinapua and Shearer. Relative abundances of nine taxa varied seasonally; however, ordination showed that both wetlands always supported discrete invertebrate communities. These results suggest that temporal fluctuations of invertebrates do not affect our ability to discriminate between wetlands.

Measuring submaximal performance parameters to monitor fatigue and predict cycling performance: a case study of a world-class cyclo-cross cyclist - Robert P. Lamberts; Gerard J. Rietjens; Hendrik H. Tijdink; Timothy D. Noakes; Michael I. Lambert (European Journal of Applied Physiology, 2010)

Phosphonate applied by trunk injection controls stem canker and decreases Phytophthora pod rot (black pod) incidence in cocoa in Sulawesi - P. J. McMahon; A. Purwantara; A. Wahab; M. Imron; S. Lambert; P. J. Keane; D. I. Guest (Australasian Plant Pathology, 2010)

Seawater and Shellfish (Geukensia demissa) Quality Along the Western Coast of Assateague Island National Seashore, Maryland: An Area Impacted by Feral Horses and Agricultural Runoff - Mary S. Lambert; Gulnihal Ozbay; Gary P. Richards (Archives of Environmental Contamination and Toxicology, 2009)

Summer precipitation in the Vosges-Black Forest-region: pre-COPS investigations - S. Argence; E. Richard; D. Lambert; P. Arbogast (Meteorology and Atmospheric Physics, 2009)

Changes in heart rate recovery after high-intensity training in well-trained cyclists - Robert P. Lamberts; Jeroen Swart; Timothy D. Noakes; Michael I. Lambert (European Journal of Applied Physiology, 2009)

Latitudinal variations in age and size at maturity among allis shad Alosa alosa populations - G. Lassalle; T. Trancart; P. Lambert; E. Rochard (Journal of Fish Biology, 2008)
Age and total length ( L T ) at maturity of allis shad Alosa alosa exhibited a significant negative latitudinal gradient over the species’ distribution range. Particular thermal conditions experienced over the distribution area could be the key factor involved to explain this negative trend.

Avian population trends in the vulnerable montane forests of the Northern Appalachians, USA - David I. King; J. Daniel Lambert; John P. Buonaccorsi; Leighlan S. Prout (Biodiversity and Conservation, 2008)

Genetic and morphological variability in the Raddia brasiliensis complex (Poaceae: Bambusoideae) - R. P. Oliveira; E. L. Borba; H. M. Longhi-Wagner; A. C. S. Pereira; S. M. Lambert (Plant Systematics and Evolution, 2008)

Potential effects of climate change on birds of the Northeast - N. L. Rodenhouse; S. N. Matthews; K. P. McFarland; J. D. Lambert; L. R. Iverson; A. Prasad; T. S. Sillett; R. T. Holmes (Mitigation and Adaptation Strategies for Global Change, 2008)

Genomic DNA sequence comparison between two inbred soybean cyst nematode biotypes facilitated by massively parallel 454 micro-bead sequencing - Sadia Bekal; J. P. Craig; M. E. Hudson; T. L. Niblack; L. L. Domier; K. N. Lambert (Molecular Genetics and Genomics, 2008)

Flanking the major Plum pox virus resistance locus in apricot with co-dominant markers (SSRs) derived from candidate resistance genes - O. Sicard; G. Marandel; J. M. Soriano; D. A. Lalli; P. Lambert; J. Salava; M. L. Badenes; A. Abbott; V. Decroocq (Tree Genetics & Genomes, 2008)

Biosystematics of Chamaecrista sect. Absus subsect. Baseophyllum (Leguminosae-Caesalpinioideae) based on allozyme and morphometric analyses - A. S. Conceição; L. P. Queiroz; S. M. Lambert; A. C. S. Pereira; E. L. Borba (Plant Systematics and Evolution, 2008)

Characterization of anticoagulant heparinoids by immunoprofiling - Tessa J. Wijnhoven; Els M. van de Westerlo; Nicole C. Smits; Joost F. Lensen; Angelique L. Rops; Johan van der Vlag; Jo H. Berden; Lambert P. van den Heuvel; Toin H. van Kuppevelt (Glycoconjugate Journal, 2008)

Genetic and morphological variation in the Bulbophyllum exaltatum (Orchidaceae) complex occurring in the Brazilian “campos rupestres”: implications for taxonomy and biogeography - P. Luz Ribeiro; E. Leite Borba; E. de Camargo Smidt; S. Mota Lambert; A. Selbach Schnadelbach; C. van den Berg (Plant Systematics and Evolution, 2008)

QTL analysis of resistance to sharka disease in the apricot (Prunus armeniaca L.) ‘Polonais’ × ‘Stark Early Orange’ F1 progeny - P. Lambert; F. Dicenta; M. Rubio; J. M. Audergon (Tree Genetics & Genomes, 2007)

Does cigarette smoking increase plasma urotensin II concentrations? - S. J. Gold; J. P. Thompson; J. P. Williams; E. E. F. Helm; J. Sadler; W. Song; L. L. Ng; D. G. Lambert (European Journal of Clinical Pharmacology, 2007)

A new method to assess water trophy and organic pollution – the Macrophyte Biological Index for Rivers (IBMR): its application to different types of river and pollution - J. Haury; M. -C. Peltre; M. Trémolières; J. Barbe; G. Thiébaut; I. Bernez; H. Daniel; P. Chatenet; G. Haan-Archipof; S. Muller; A. Dutartre; C. Laplace-Treyture; et al. (Hydrobiologia, 2006)

Genetic Structure in Tunisian Apricot, Prunus armeniaca L., Populations Propagated by Grafting: A Signature of Bottleneck Effects and Ancient Propagation by Seedlings - B. Khadari; L. Krichen; P. Lambert; M. Marrakchi; J. M. Audergon (Genetic Resources and Crop Evolution, 2006)

Cell and tissue responses of a range of Urotensin II analogs at cloned and native urotensin II receptors. Evidence for coupling promiscuity - Wei Song; John McDonald; Valeria Camarda; Girolamo Calo; Remo Guerrini; Erika Marzola; Jonathan P. Thompson; David J. Rowbotham; David G. Lambert (Naunyn-Schmiedeberg's Archives of Pharmacology, 2006)

A stage‐structured model to predict the effect of temperature and salinity on glass eel Anguilla anguilla pigmentation development - C. Briand; D. Fatin; E. Ciccotti; P. Lambert (Journal of Fish Biology, 2005)
The pigmentation development process of glass eels Anguilla anguilla from stage V B to VI A3 was modelled by gamma cumulative functions. These functions varied with respect to the factors temperature and salinity whose effects were adjusted by beta functions. Temperature was shown to accelerate pigmentation, while salinity acted as a secondary factor slowing down the pigmentation. The model fits the development of 15 samples kept at various temperatures and salinities in the Vilaine River, as well as samples monitored at other dates and places in Europe. It allows the prediction of the duration of estuarine residency for glass eels, in winter and spring, in the Atlantic estuaries.

Analogues of virus resistance genes map to QTLs for resistance to sharka disease in Prunus davidiana - V. Decroocq; M. Foulongne; P. Lambert; O. Le. Gall; C. Mantin; T. Pascal; V. Schurdi-Levraud; J. Kervella (Molecular Genetics and Genomics, 2005)

Effect of Extra-Pair Paternity on Effective Population Size in a Reintroduced Population of the Endangered Hihi, and Potential for Behavioural Management - Isabel Castro; Karen M. Mason; Doug P. Armstrong; David M. Lambert (Conservation Genetics, 2004)

Genetic linkage maps of two apricot cultivars (Prunus armeniaca L.) compared with the almond Texas × peach Earlygold reference map for Prunus - P. Lambert; L. S. Hagen; P. Arus; J. M. Audergon (Theoretical and Applied Genetics, 2004)

Factors affecting recruitment of glass eels into the Grey River, New Zealand - D. J. Jellyman; P. W. Lambert (Journal of Fish Biology, 2003)
The arrival pattern of glass eels of the shortfin eel Anguilla australis and longfin eel Anguilla dieffenbachii was studied over a two successive migration seasons in the Grey River, South Island, New Zealand. Fishing was carried out on selected nights during September to November, for 3 h per night during 2000 and 2001. The number of shortfin glass eels exceeded longfins in both years; earliest glass eels (September) were larger than later glass eels (November), and longfins larger than shortfins, but there were significant differences in size between years for both species. Environmental variables affecting recruitment differed between years, but common variables for both years were sampling date, time after high tide (incoming tide preferred), time after sunset and moon phase; the influence of moon phase appeared to be expressed both through tides (spring tides preferred) and moonlight. During the year of higher discharge variability, both increasing discharge and increased turbidity were also important.

AM404 and VDM 11 non-specifically inhibit C6 glioma cell proliferation at concentrations used to block the cellular accumulation of the endocannabinoid anandamide - Kent-Olov Jonsson; Anna Andersson; Stig O. P. Jacobsson; Séverine Vandevoorde; Didier M. Lambert; Christopher J. Fowler (Archives of Toxicology, 2003)

Ecoregional differences in macrophyte and macroinvertebrate communities between Westland and Waikato: Are all New Zealand lowland streams the same? - I. C. Duggan; K. J. Collier; P. D. Champion; G. F. Croker; R. J. Davies‐Colley; P. W. Lambert; J. W. Nagels; R. J. Wilcock (New Zealand Journal of Marine and Freshwater Research, 2002)
We characterised water chemistry, aquatic habitat, macrophytes, and invertebrate assemblages in eight lowland streams—five in Westland, South Island, and three in the Waikato, North Island, New Zealand. Factors influencing invertebrate community structure over large (between ecoregions) and small (within an ecoregion) spatial scales were investigated. The Westland sites had generally lower nutrient concentrations, conductivity, and water clarity, and coarser substrates than the Waikato sites, reflecting differences in geological history, hydrology, and land‐use intensity. The macrophyte communities in each region were very different in species composition and structure, but seasonal abundance patterns in both regions were fairly typical of New Zealand streams in general. Alien obligate submerged macrophyte species were absent from the Westland lowland stream sites, and may partly reflect the isolated nature of this region where colonisation by asexual macrophytes would be difficult. Waikato stream invertebrate faunas were dominated by molluscs (mainly Potamopyrgus ) and crustaceans (mainly amphipods), whereas Epheme‐roptera, Trichoptera, and Coleoptera taxa dominated the Westland stream faunas. The overall structure of invertebrate assemblages appeared to be influenced by a combination of regional differences in substrate type, nutrient concentrations, water clarity, and macrophyte cover. Westland streams with more upstream pastoral development had higher proportions of molluscs than those with predominantly forested or scrub catchments. Our study suggests that large‐scale ecoregional differences may override smaller‐scale land‐use effects on lowland stream invertebrate communities, and that management strategies should be developed on an ecoregional basis for lowland stream ecosystems.

Foliar resistance to late blight in potato clones evaluated in national trials in 1997 - K. G. Haynes; B. J. Christ; D. P. Weingartner; D. S. Douches; C. A. Thill; G. Secor; W. E. Fry; D. H. Lambert (American Journal of Potato Research, 2002)

Genetic diversity in apricot revealed by AFLP markers: species and cultivar comparisons - L. Hagen; B. Khadari; P. Lambert; J.-M. Audergon (Theoretical and Applied Genetics, 2002)

Increased protein tyrosine phosphorylation in apoptotic neural cell death due to microtubule perturbations - Brett A. Chromy; Mary P. Lambert; William L. Klein (Neurotoxicity Research, 2000)

A novel restriction fragment length polymorphism for petrels or tube‐nosed seabirds - C. D. Millar; G. A. Taylor; P. J. Moore; J. L. Halverson; D. M. Lambert (Molecular Ecology, 2000)

Variation in growth rate and reproductive output in British populations of the dorid nudibranch Adalaria proxima : consequences of restricted larval dispersal? - W. J. Lambert; C. D. Todd; J. P. Thorpe (Marine Biology, 2000)

Influence of acute submaximal exercise on T-lymphocyte suppressor cell function in healthy young men - Charles P. Lambert; Michael G. Flynn; William A. Braun; Eleni Mylona (European Journal of Applied Physiology, 2000)

Formulation Development and Antitumor Activity of a Filter-Sterilizable Emulsion of Paclitaxel - Panayiotis P. Constantinides; Karel J. Lambert; Alex K. Tustian; Brian Schneider; Salima Lalji; Wenwen Ma; Bryan Wentzel; Dean Kessler; Dilip Worah; Steven C. Quay (Pharmaceutical Research, 2000)

In Vitro Synergy Between Ranitidine Bismuth Citrate and Tetracycline or Clarithromycin Against Resistant Strains of Helicobacter pylori - P. D. Midolo; J. R. Lambert; T. G. Kerr; W. Tee (European Journal of Clinical Microbiology & Infectious Diseases, 1999)

Missense mutations in hMLH1 associated with colorectal cancer - T. Liu; P. Tannergård; P. Hackman; C. Rubio; G. Lindmark; U. Kressner; D. Hellgren; B. Lambert; A. Lindblom (Human Genetics, 1999)

Missense mutations in hMLH1 associated with colorectal cancer - T. Liu; P. Tannergård; P. Hackman; C. Rubio; G. Lindmark; U. Kressner; D. Hellgren; B. Lambert; A. Lindblom (Human Genetics, 1999)

Sustainable management of native and exotic plantations in Australia - John Turner; Stanley P. Gessel; Marcia J. Lambert (New Forests, 1999)

Slant Column Measurements of O3 and NO2 During the NDSC Intercomparison of Zenith-Sky UV-Visible Spectrometers in June 1996 - H. K. Roscoe; P. V. Johnston; M. Van Roozendael; A. Richter; A. Sarkissian; J. Roscoe; K. E. Preston; J-C. Lambert; C. Hermans; W. DeCuyper; S. Dzienus; T. Winterrath; et al. (Journal of Atmospheric Chemistry, 1999)

Climatic and anthropogenic influence on the stable isotope record from bulk carbonates and ostracodes in Lake Neuchâ, Switzerland, during the last two millennia - M.L. Filippi; P. Lambert; J. Hunziker; B. Kübler; S. Bernasconi (Journal of Paleolimnology, 1999)

Gonad histology and plasma steroid profiles in wild New Zealand freshwater eels (Anguilla dieffenbachii and A. australis) before and at the onset of the natural spawning migration. I. Females* - P. Mark Lokman; Gerard J. Vermeulen; Jan G.D. Lambert; Graham Young (Fish Physiology and Biochemistry, 1998)

The role of glutathione and cysteine conjugates in the nephrotoxicity of o-xylene in rats - G. Morel; P. Bonnet; B. Cossec; S. Morel; C. Cour; A. M. Lambert; M. B. Roure; M. T. Brondeau (Archives of Toxicology, 1998)

Phenotypic stability of resistance to late blight in potato clones evaluated at eight sites in the United States - K. G. Haynes; D. H. Lambert; B. J. Christ; D. P. Weingartner; D. S. Douches; J. E. Backlund; G. Secor; W. Fry; W. Stevenson (American Journal of Potato Research, 1998)

Evidence for several genomes in Helianthus - K. Sossey-Alaoui; H. Serieys; M. Tersac; P. Lambert; E. Schilling; Y. Griveau; F. Kaan; A. Bervillé (Theoretical and Applied Genetics, 1998)

Application of a PCR-based test for detection of potato late blight and pink rot in tubers - P. W. Tooley; M. M. Carras; D. H. Lambert (American Journal of Potato Research, 1998)

Use of Pulsed Field Gel Electrophoresis to Determine the Source of Microbial Contamination of Central Venous Catheters - M. A. Livesley; S. E. Tebbs; H. A. Moss; M. H. Faroqui; P. A. Lambert; T. S. J. Elliott (European Journal of Clinical Microbiology & Infectious Diseases, 1998)

Use of pulsed field gel electrophoresis to determine the source of microbial contamination of central venous catheters - M. A. Livesley; S. E. Tebbs; H. A. Moss; M. H. Faroqui; P. A. Lambert; T. S. J. Elliott (European Journal of Clinical Microbiology & Infectious Diseases, 1998)

Spectroscopic Characterization of Humic-Like Substances in Airborne Particulate Matter - N. Havers; P. Burba; J. Lambert; D. Klockow (Journal of Atmospheric Chemistry, 1998)

Mapping sediment acoustic impedance using remote sensing acoustic techniques in a shallow-water carbonate environment - Donald J. Walter; Douglas N. Lambert; David C. Young; Kevin P. Stephens (Geo-Marine Letters, 1997)

s of papers presented at the 81st annual meeting of The Potato Association of America Charlottetown, P.E.I., Canada August 3 – 7, 1997 - S. T. Ali-Khan; C. Hetner; L. Ladislav; V. Currie; Walter J. Arsenault; A. Naseer Aziz; Janet E. A. Seabrook; George C. C. Tai; J. B. Bamberg; Alfonso H. del Rio; Max Martin; J. B. Bamberg; et al. (American Journal of Potato Research, 1997)

Monitoring changes of ice streams using time series of satellite-altimetry-based digital terrain models - Ute C. Herzfeld; Craig S. Lingle; Cecily Freeman; Chris A. Higginson; Michael P. Lambert; Li-Her Lee; Vera A. Voronina (Mathematical Geosciences, 1997)

Exon skipping in the sterol 27-hydroxylase gene leads to cerebrotendinous xanthomatosis - A. Verrips; Gerry C. H. Steenbergen-Spanjers; J. A. F. M. Luyten; R. A. Wevers; John H. J. Wokke; Fons J. M. Gabrels; Bert G. Wolthers; Lambert P. W. J. van den Heuvel (Human Genetics, 1997)

Lack of association between five polymorphisms in the human glucocorticoid receptor gene and glucocorticoid resistance - J. W. Koper; Ronald P. Stolk; Pieter de Lange; Nannette A. T. M. Huizenga; Gerd-Jan Molijn; Huibert A. P. Pols; Diederick E. Grobbee; Michael Karl; F. H. de Jong; Albert O. Brinkmann; Steven W. J. Lamberts (Human Genetics, 1997)

Cost-effectiveness of screening blood donors for hepatitis C and non-A, non-B, non-C hepatitis - C. Colin; P. Vergnon; A. M. Jullien; S. Excoffier; Y. Matillon; C. Trepo; J. P. Aymard; D. Bastit; M. L. Bidet; R. Breviere; F. Chenais; F. Hau; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 1997)

Specifying the introgressed regions from H. argophyllus in cultivated sunflower (Helianthus annuus L.) to mark Phomopsis resistance genes - G. Besnard; Y. Griveau; M. C. Quillet; H. Serieys; P. Lambert; D. Vares; A. Bervillé (Theoretical and Applied Genetics, 1997)

Phosphatidylcholine synthesis in isolated type II pneumocytes from ozone-exposed rats - Leendert van Bree; Henk P. Haagsman; Lambert M. G. van Golde; Pieter J. A. Rombout (Archives of Toxicology, 1988)

The fine structure of frozen etched Nitrobacter cells - A. P. Gool; R. Lambert; H. Laudelout (Archives of Microbiology, 1969)